Study of crystal shapes in high alumina cement clinker - Neo, Zhi Wei, 1985-; Mohamed Noor Mohammad,lcsupervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2009